ASPEK PERTANGGUNGJAWABAN TENAGA MEDIS NON AHLI ATAS TERJADINYA MALPRAKTIK DALAM OPERASI BESAR (Analisis Putusan Pengadilan Negeri Madiun Nomor 5/Pdt.G/2015) - Prestiana, Yuan Okta (Res Judicata, 2020)
Malpractice cases have always been the most frequently encountered problems in health law and health services. Malpractice occurs due to violations of rules by medical personnel. One form of violation that occurred was the implementation of large operations by non-skilled medical personnel. This legal research analyzes the forms of accountability of non-skilled medical personnel in the event of malpractice in major operations. The method used in this study is normative legal research using the statutory approach, conceptual approach and case approach. The results showed that the accountability of medical personnel who were not a team of experts when carrying out major operations included civil liability and criminal liability.